2021
DOI: 10.1162/qss_a_00155
|View full text |Cite
|
Sign up to set email alerts
|

Continued use of retracted papers: Temporal trends in citations and (lack of) awareness of retractions shown in citation contexts in biomedicine

Abstract: We present the first database-wise study on the citation contexts of retracted papers, which covers 7,813 retracted papers indexed in PubMed, 169,434 citations collected from iCite, and 48,134 citation contexts identified from the XML version of the PubMed Central Open Access Subset. Compared with previous citation studies that focused on comparing citation counts using two time frames (i.e., pre-retraction and post-retraction), our analyses show the longitudinal trends of citations to retracted papers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
2
26
0
1
Order By: Relevance
“…Over 94% of post-retraction citations in biomedicine do not demonstrate awareness that the cited item was retracted [ 24 ]. Users' typical citation workflows may involve citing preprints, reusing downloaded copies, citing older works contained in their reference managers, and copying citations from their own or others' previous bibliographies [ 21 , 22 ].…”
Section: Results: the Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 94% of post-retraction citations in biomedicine do not demonstrate awareness that the cited item was retracted [ 24 ]. Users' typical citation workflows may involve citing preprints, reusing downloaded copies, citing older works contained in their reference managers, and copying citations from their own or others' previous bibliographies [ 21 , 22 ].…”
Section: Results: the Recommendationsmentioning
confidence: 99%
“…When citing retracted papers, authors frequently do not indicate retraction status in bibliographies or in-text citations. A study of citations to retracted papers in PubMed found that only 5.4% of post-retraction citations acknowledged that the paper they were citing was retracted [ 24 ]. A smaller study, focused on two retracted COVID-19 articles, found that 52.5% of citations did not acknowledge the fact that they were retracted despite the widespread media attention that these retractions received [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Across the rapidly growing landscape of preprint servers and journals that currently exist, it is unlikely that this occurs reliably. This failure to back-propagate critical information not only leaves preprint readers in the dark about the invalidation of some research, but it could also exacerbate the problem of papers being cited persistently after retraction [ 22 , 23 ]. To be clear, the problem is not with the occurrence of retractions themselves–which should be viewed as an indication that corrective systems are working properly [ 24 ]–but, rather, with the persistence of these papers in the literature due to their continued citation.…”
Section: Discussionmentioning
confidence: 99%
“…Today, content-based citation analysis is used for many different purposes, from citation recommendation systems to citation sentiment analysis (Hsiao & Schneider, 2022;Leng, 2022;Wang et al, 2020;Wang et al, 2022;Yan et al, 2020;Zhang & Zhu, 2022). The future of content-based citation analysis lies in the work to be done with computational linguistic techniques.…”
Section: A Need To Go Beyond Counting: Content-based Citation Analysismentioning
confidence: 99%